2017
DOI: 10.3389/fpsyg.2017.00580
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Control Over Action for Food in Obese versus Healthy-weight Individuals

Abstract: In the current study we examined an associative learning mechanism by which food cues (signaling low- versus high-calorie food) can bias instrumental responses directed toward those foods. To investigate the clinical relevance of this mechanism, we used a computerized Pavlovian-to-instrumental transfer task and compared performance of 19 severely obese individuals to that of 19 healthy-weight controls matched for age, education and gender. During the response-priming test we exposed participants to both food p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 49 publications
5
48
0
Order By: Relevance
“…This line of research stresses the importance, therefore, of carefully regulating advertising aimed at selling unhealthy, high‐calorie snacks – especially when aimed at children. In related research, we have demonstrated that these cueing effects are indeed stronger with high‐calorie than with low‐calorie snack cues in adolescents (Watson et al ., ) and severely obese individuals (Watson et al, ). Combined with the demonstration that this associative (PIT) mechanism is not flexibly modulated by changes in motivation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This line of research stresses the importance, therefore, of carefully regulating advertising aimed at selling unhealthy, high‐calorie snacks – especially when aimed at children. In related research, we have demonstrated that these cueing effects are indeed stronger with high‐calorie than with low‐calorie snack cues in adolescents (Watson et al ., ) and severely obese individuals (Watson et al, ). Combined with the demonstration that this associative (PIT) mechanism is not flexibly modulated by changes in motivation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the data are interesting in light of a recent experiment by Watson et al (2017), who found that obese participants showed stronger PIT effects for high-calorie foods than low-calorie foods. The authors suggested that, because outcome value was established before training, obese participants might have formed weaker Pavlovian and instrumental links with the low-calorie foods than the high-calorie foods.…”
Section: Discussionmentioning
confidence: 81%
“…was superimposed on the Pavlovian stimulus, above the four outcome options ("CRISPS", "POPCORN", "CASHEWS" and "NACHOS"). The four options were arranged vertically and were ordered randomly on each trial, and participants selected an option using the mouse (see e.g., Watson, Wiers, Hommel, Gerdes, & de Wit, 2017, for a similar procedure). The correct outcome (see Table 1) was then presented, regardless of the participant's response.…”
mentioning
confidence: 99%
“…Garbusow et al, ; Garbusow et al, ; Hogarth & Chase, ; Hogarth & Chase, ; Martinovic et al, ; Vogel et al, ) or food‐related behaviour (e.g. Colagiuri & Lovibond, ; Watson, Wiers, Hommel, Gerdes & de Wit, ). A specific PIT effect is characterized by an increase of instrumental responding for a reward outcome in the presence of a conditioned stimulus associated with that outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A specific PIT effect is characterized by an increase of instrumental responding for a reward outcome in the presence of a conditioned stimulus associated with that outcome. For example, Watson et al () found for obese individuals that a stimulus associated with high‐calorie food increased responding for high‐calorie foods demonstrating that aberrant eating behaviour may be influenced by conditioned food‐related stimuli. Consequently, the PIT paradigm seems to be a useful tool to investigate whether in AN, the confrontation with conditioned disorder‐compatible stimuli triggers pathological behaviour to achieve the goal of weight loss.…”
Section: Introductionmentioning
confidence: 99%